The Postoperative Analgesic Effect of Ultrasound-Guided Bilateral Transversus Abdominis Plane Combined with Rectus Sheath Blocks in Laparoscopic Hepatectomy: A Randomized Controlled Study - Lu X; Yu P; Ou C; Wang J; Zhou Z; Lai R (Dove Medical Press, 2020)
Xiaoyun Lu1,2 *,* Ping Yu1,2 *,* Chaopeng Ou1,2 *,* Junchao Wang,1,2 Zhongguo Zhou,1,3 Renchun Lai1,2 1Collaborative Innovation Center for Cancer Medicine, State Key Laboratory of Oncology in South China, Sun Yat-Sen University Cancer Center, Guangzhou, Guangdong, People’s Republic of China; 2Department of Anesthesiology, Sun Yat-Sen University Cancer Center, Guangzhou, Guangdong, People’s Republic of China; 3Department of Liver Surgery, Sun Yat-Sen University Cancer Center, Guangzhou, Guangdong, People’s Republic of China*These authors contributed equally to this work.Correspondence: Zhongguo Zhou; Renchun Lai Email zhouzhg@sysucc.org.cn; lairench@sysucc.org.cnBackground: Our aim was to investigate the postoperative analgesic effect of ultrasound (US)-guided bilateral transversus abdominis plane (TAP) blocks combined with rectus sheath blocks (RSBs) in laparoscopic hepatectomy.Patients and Methods: A total of 126 patients were allocated into two groups for analysis. Group 1 (n = 63) did not receive any local anesthetics. Group 2 (n = 63) received US-guided bilateral TAP blocks and RSBs using 20 mL 0.25% ropivacaine in each block. Postoperative pain scores, the dose of intraoperative remifentanil, 24 h consumption of oxycodone, adverse events such as postoperative dizziness, nausea and vomiting, and the length of postoperative hospital stay were recorded.Results: In the postanesthesia care unit, patients in group 2 had significantly lower pain visual analog scale (VAS) scores at rest than those in group 1 (P < 0.001). The VAS scores both at rest and during movement were significantly lower in group 2 than in group 1 at 2, 4 and 6 h postoperatively (all P < 0.001). There was no difference in VAS scores between the two groups at rest 24 h postoperatively (P = 0.477). However, the VAS score during movement at 24 h in group 2 was significantly lower than that in group 1 (P < 0.001). No significant differences in the incidence of adverse events or the dose of intraoperative remifentanil were observed between the two groups (all P > 0.05). Patients in group 2 had a significantly lower 24 h consumption of oxycodone than patients in group 1 (P < 0.001). The mean length of postoperative hospital stay of group 2 was shorter than that of group 1 (P = 0.032).Conclusion: US-guided bilateral TAP blocks combined with RSBs provide effective postoperative analgesia for laparoscopic hepatectomy, and they could shorten the postoperative hospital stay without increasing the incidence of adverse events from opioids.Keywords: laparoscopic hepatectomy, analgesia, transversus abdominis plane block, rectus sheath block, ultrasound